2011
DOI: 10.1111/j.1365-3024.2010.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the Plasmodium falciparum rhoptry protein RAP‐2/RSP‐2 in relation to anaemia in Cameroonian children

Abstract: Previous studies have implicated reactive antibodies to the low molecular weight rhoptry-associated proteins (RAP-1, RAP-2/RSP-2 and RAP-3) in erythroid cell destruction during Plasmodium falciparum infection. In this pilot study, the frequency, specificity and functional capacity of naturally acquired anti-RAP-2/RSP-2 antibodies were investigated in the sera of anaemic and nonanaemic malaria-infected Cameroonian children. All sera recognized RAP-2/RSP-2 by FACS, irrespective of the clinical status of the subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…On the other hand, experiments conducted with P. falciparum have shown that the tagging of the surface of noninfected RBCs by parasite proteins, as well as the tagging of the erythroid precursor cells in bone marrow, may elicit a specific antibody response, triggering phagocytosis and complement activation and inducing the clearance of these cells (128)(129)(130)(131). These data suggest that specific immune responses induced by some parasite antigens may contribute to malaria pathogenesis, playing a role in the development of malarial anemia.…”
Section: Antibodies and Malaria: Protective Or Pathogenic?mentioning
confidence: 93%
“…On the other hand, experiments conducted with P. falciparum have shown that the tagging of the surface of noninfected RBCs by parasite proteins, as well as the tagging of the erythroid precursor cells in bone marrow, may elicit a specific antibody response, triggering phagocytosis and complement activation and inducing the clearance of these cells (128)(129)(130)(131). These data suggest that specific immune responses induced by some parasite antigens may contribute to malaria pathogenesis, playing a role in the development of malarial anemia.…”
Section: Antibodies and Malaria: Protective Or Pathogenic?mentioning
confidence: 93%
“…Studies in children with SA revealed that immune complex (IC) may contribute an important role in erythrocyte destruction leading to development of malarial anemia (Mibei et al 2005). Also, experiments with Pf showed that tagging the surface of uninfected RBCs and erythroid precursor cells in bone marrow by parasite proteins may elicit a specific antibody response, triggering phagocytosis and complement activation and inducing the clearance of these cells, eventually leading to anemia (Awah et al 2011(Awah et al , 2009Layez et al 2005;Sterkers et al 2007). It is clearly evident from the results of this study, that the circulatory levels of anti-MSP-1 19 antibodies were higher in patients with increased anemic severity during Pv and Pf infections.…”
Section: ; Polleymentioning
confidence: 99%
“…To compound the problem, reduced glutathione, which is necessary for protecting red cells against damaging oxygen species, is reported to be depleted in vivax malaria [93,122]. Infection with P. falciparum causes altered expression of complement components and deposition of parasite proteins on infected and uninfected red blood cells [88,92] (the latter sometimes associated with presence of specific immunoglobulins); facilitating opsonization and complement-mediated phagocytosis [89,91,123]. It is unknown whether these processes also occur in vivax anaemia.…”
Section: Introductionmentioning
confidence: 99%